Healthcare burden and reimbursement of hospitalization during chemotherapy for adults with Ph-negative relapsed or refractory B-cell precursor acute lymphoblastic leukemia in France: a retrospective chart review. (1st November 2016) - Dombret, Hervé; Thomas, Xavier; Chevallier, Patrice; Nivot, Edwige; Reitan, John; Barber, Beth; Barlev, Arie; Mohty, Mohamad
Abstract: Objective: Philadelphia chromosome negative [Ph(−)] relapsed or refractory (R/R) B-precursor acute lymphoblastic leukemia (ALL) is an extremely rare condition requiring intensive treatment. This retrospective chart review aimed to quantify hospitalizations and reimbursement in this patient population in France. Methods: Patients aged ≥18 years and with at least one hospitalization for Ph(−) R/R B-precursor ALL were included in the study. They were relapsed with first remission lasting <12 months, relapsed after first salvage therapy, relapsed any time after hematopoietic stem cell transplant (HSCT), or were refractory to initial or salvage therapy. Data were collected from the index date (first diagnosis of R/R ALL) until death or loss to follow-up. The chemotherapy period was defined as the first chemotherapy date after the index date to the earliest of death, loss to follow-up, last chemotherapy dose plus 30 days, or initiation of HSCT. The primary outcome was the percentage of time hospitalized during the chemotherapy period. Results: Thirty-three patients were included, with a mean age of 49 years. The mean proportion of time spent in the hospital during the chemotherapy period was 46% (95% CI =34–57%). Patients had a mean of 2.2 (SD =1.5) inpatient hospitalizations and the mean length of stay per hospitalization was 16.8 (SD =14.8) days. During the chemotherapy period, the mean amount reimbursed per hospitalization was €31 067 (SD = €4850) and the total hospitalization reimbursement per patient was €68 344. From the index date to death, excluding HSCT, the total reimbursement per patient was €108 873. Limitations: The sample size was small, although this was expected given the rarity of the patient population. Conclusions: Adults with Ph(−) R/R B-precursor ALL had repeated and prolonged hospitalizations during salvage chemotherapy. Approximately half the follow-up period was spent in the hospital, and this time was associated with high economic burden in France.